HUBUNGAN AKREDITASI PUSKESMAS DENGAN PELAKSANAAN UPAYA KESEHATAN DI KABUPATEN KONAWE SELATAN - abdul samad (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2020)
Healthy Indonesian Program with the goal of improving the health and nutrition status of the community through health efforts and community empowerment is one of the objectives of the National Medium Term development plan in the year 2015-2019. The next Community Health Center called the Health Center is a health service facility that conducts public health and first-rate public health efforts, focusing more on promotional and preventive efforts, to achieve the highest levels of public health in its area of ​​work. The implementation of the Healthcare accreditation policy has a significant impact on the management of public health services and employee productivity. Therefore, accreditation system will be guaranteed to ensure the quality of individual and community health care efforts. The purpose of this research is to know the relationship of Puskesmas's accreditation to personal health efforts and public health efforts. This type of research is quantitative research with cross sectional study design. The population in this study was as much as 60 people while a large sample of 55 people were taken on a random sampling cluster. Data analyzed using Chi square test and phi coefficient. The results showed that there was a link between the status of accreditation with individual health and public health efforts, where the value of P-value = 0,000 < 0.05. Keywords: Accreditation, Personal Health Efforts And Public Medical Efforts